Pengaruh Penerapan Model Pembelajaran Kooperatif Terhadap Hasil Belajar Matematika Dan Self-Confidence Siswa Kelas XI IPA - Asdar; Talib, Ahmad; Sofyan, Muh. (Issues in Mathematics Education (IMED), 2018)
The research is eksperiment hat has purpose to know: (1) Mathematics Learning Achievement description of student who is thought by using cooperative learning type group investigation dan convensional learning; (2) Mathematics Learning Self-Confidence description of student who is thought by using cooperative learning type group investigation dan convensional learning; (3) influence of cooperative learning type group investigation towards Mathematics Learning Self-Confidence and Achievement Of Students at Class XI IPA Senior High School Muhammadiyah Kalosi. Researcher choose two classes by using random sampling. The data are obtained from observation, quetionnaire, dan test result. The data is analyzed by using descriptive statistical analysis dan infrential statistical analysis. The result is analyzed by using descriptive mean of achievement value and Self-Confidence score of student by using cooperative learning type Group Investigation dan convensional learning. The result in infrential statistical analysis show that student mathematics learning self-confidence and achievement who is taught by using cooperative learning type group investigation is better than student mathematics learning achievement and self-confidence who is taught by using convensional learning.